Primary spinal extradural hydatid cyst causing paraplegia - Jaiswal Sushila; Jaiswal Awadhesh; Jain Manoj; Behari Sanjay; Pandey Rakesh (Wolters Kluwer Medknow Publications, 2009)
Spinal hydatid disease is an uncommon cause of spinal cord compression and it constitutes 1% of all cases of hydatid disease. The authors present a case of a 21-year-old female presenting with rapid onset paraplegia caused by pathologically confirmed by extradural spinal hydatid cyst. Patient had marked improvement following surgical intervention. The case is discussed and the relevant literature is briefly reviewed.